Exploration of the binding between cuminol and bovine serum albumin through spectroscopic, molecular docking and molecular dynamics methods. Issue 22 (12th December 2022) - Ali, Mohd Sajid; Rehman, Md Tabish; Al-Lohedan, Hamad A.; AlAjmi, Mohamed Fahad
Abstract: Cuminol (4-Isopropylbenzyl alcohol), found in the essential oils of several plant sources, is an important constituent of several cosmetics formulations. The interaction of cuminol with model plasma protein bovine serum albumin was studied in this paper. The experimental studies were mainly carried out using fluorescence spectrophotometry aided with UV visible and CD spectroscopies. Intrinsic fluorescence measurements showed that there was a weak binding between cuminol and BSA. The mechanism of binding involved static quenching with around 1:1 binding. The binding was chiefly supported by hydrophobic forces although a little contribution of hydrogen bonding was also found in the interaction and the values of enthalpy change were negative with positive entropy change. The secondary structure of BSA didn't change significantly in presence of low concentrations of cuminol, however, partial unfolding of the former taken place when the concentration of the latter increased. Molecular docking analyses showed cuminol binds at the intersection of subdomains IIA and IIIA, i.e. its binding site is in between Sudlow sites I and II. Molecular dynamics simulations results have shown that BSA forms a stable complex with cuminol and the structure of the former didn't change much in presence of later. Communicated by Ramaswamy H. Sarma